Effectiveness of non-formal programs in Nigeria: how competent are the learners in life skills? (2009)
In order to achieve the Millennium Development Goals (MDGs), Nigeria adopts both formal and non-formal approaches to provide basic education for its citizenry. Thus , to determine the effectiveness of the non-formal approach in providing basic education in Nigeria, this study examines the competency level of Nigerian non-formal education learners on a life-skills achievement test. The test was administered to a sample of 876 learners. The competency level of life-skills of the majority of the learners was below the national benchmark (50%). Rural dwellers were more competent than urban dwellers and young learners were more competent than old learners.